Disciplinary diversity in marine sciences: the urgent case for an integration of research. (20th November 2017) - Markus, Till; Hillebrand, Helmut; Hornidge, Anna-Katharina; Krause, Gesche; Schlüter, Achim
Abstract: Recent events and trends in international relations are making it necessary for scientists to design their projects in ways that can integrate disciplinary perspectives and learn how to communicate their results in governance processes. Some examples of settings in which such skills would be needed are the debates about the political and legal relevance of the "Anthropocene" as a concept, the establishment and implementation of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), the recent International Court of Justice's decision on what constitutes "scientific purpose" under the Whaling Convention, and the ongoing international efforts to regulate deep seabed mining activities. These events reveal an acceleration of growing environmental, distributional, and geostrategic conflicts over ocean resources which are changing the character of marine research. For some time now marine sciences have recognized the interdependence of social and ecological systems and the cumulative effects of multiple environmental pressures. In addition, we observe that the relationship between science and policy-making is rapidly changing in a process which we refer to here as the internationalization of knowledge, and that scientific research activities and results are progressively being internationally contested. Altogether these developments constitute extrinsic constraints that render transcending disciplinary boundaries a conditio sine qua non for future marine research. Better comprehension of these trends and their implications may help us to understand marine science's functioning in the near future, particularly the relationship between disciplines involved.